Toksične snovi v lesovih - Tišler, Vesna (Les (Ljubljana), 2001)
In the article the most toxical substances in wood species like its properties, its influence on human health, methods of diagnosticing and its identification are being presented. Also are presented the homegrown and foreign tree species, especially tropical ones, which have influence on workers health.
Keywords: les; strupi